EFFECTIVENESS OF LAND AND WATER RESOURCES OF FARMS USAGE - Madaminova , Shoirakhan Komiljon qizi (Educational Research in Universal Sciences, 2023)
In agriculture, land is the main means of production, and production is formed through the cultivation of land by people. Land appears in agriculture as an object of labor (as an object that directs labor) and as a tool of labor (plants develop as a result of creating the necessary biological conditions on the ground). Land is the main wealth of any nation.